Targeting caspase-8: a new strategy for combating hepatocellular carcinoma - Chen, Haoran; Lin, Yumeng; Chen, Jie; Luo, Xuemei; Kan, Yubo; He, Yuqi; Zhu, Renhe; Jin, Jiahui; Li, Dongxuan; Wang, Yi; Han, Zhongyu (Frontiers in Immunology, 2024)
Hepatocellular carcinoma (HCC) represents the most prevalent form of primary liver cancer and has a high mortality rate. Caspase-8 plays a pivotal role in an array of cellular signaling pathways and is essential for the governance of programmed cell death mechanisms, inflammatory responses, and the dynamics of the tumor microenvironment. Dysregulation of caspase-8 is intricately linked to the complex biological underpinnings of HCC. In this manuscript, we provide a comprehensive review of the regulatory roles of caspase-8 in apoptosis, necroptosis, pyroptosis, and PANoptosis, as well as its impact on inflammatory reactions and the intricate interplay with critical immune cells within the tumor microenvironment, such as tumor-associated macrophages, T cells, natural killer cells, and dendritic cells. Furthermore, we emphasize how caspase-8 plays pivotal roles in the development, progression, and drug resistance observed in HCC, and explore the potential of targeting caspase-8 as a promising strategy for HCC treatment.